Advances of multi-omics applications in hepatic precancerous lesions and hepatocellular carcinoma: The role of extracellular vesicles - Lu, Xiaona; Li, Yuyao; Li, Yue; Zhang, Xuemei; Shi, Jia; Feng, Hai; Gao, Yueqiu; Yu, Zhuo (Frontiers in Molecular Biosciences, 2023)
Due to the lack of distinct early symptoms and specific biomarkers, most patients with hepatocellular carcinoma (HCC) are usually diagnosed at advanced stages, rendering the treatment ineffective and useless. Therefore, recognition of the malady at precancerous lesions and early stages is particularly important for improving patient outcomes. The interest in extracellular vesicles (EVs) has been growing in recent years with the accumulating knowledge of their multiple cargoes and related multipotent roles in the modulation of immune response and tumor progression. By virtue of the rapid advancement of high-throughput techniques, multiple omics, including genomics/transcriptomics, proteomics, and metabolomics/lipidomics, have been widely integrated to analyze the role of EVs. Comprehensive analysis of multi-omics data will provide useful insights for discovery of new biomarkers and identification of therapeutic targets. Here, we review the attainment of multi-omics analysis to the finding of the potential role of EVs in early diagnosis and the immunotherapy in HCC.